Rand’s Legal Republicanism - Dyzenhaus, David (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
Justice Rand’s judgment in Roncarelli v. Duplessis is best understood in light of recent political and legal theory that argues for the importance of the republican ideal of non-domination for in it he sets out an account of the rule of law that gives clear expression to that ideal, one founded in a more basic ideal of respect for persons. As Rand understood things, Roncarelli was a member of a disliked minority, who was singled out for persecution when he had done nothing more than exercise his rights as a free and equal subject of the law. Those who singled him out for persecution sought to achieve their ends through law.The author argues that since government under law is valuable because it helps to secure non-domination (the rule of law rather than the arbitrary rule of men), to use law to single out an individual for domination is, as Duplessis discovered, rather a complex business. No matter one’s grip on power, one might find that one’s ends simply do not count as public ends within a system of public law because such a system is predicated on respect for the persons who are subject to its authority.